What Moves the Primary Stock and Bond Markets? Influence of Macroeconomic Factors on Bond and Equity Issues in Malaysia and Korea - Rashid Ameer (Asian Academy of Management Journal of Accounting and Finance, 2007)
This paper examines the impact of macroeconomic factors on the stock and bond market activities in two Asian countries. We examine the influence of interest rate changes, expected inflation rate, and stock market returns on aggregate stock and bond issuance in Malaysia and Korea. Using vector autoregressive models (VARs) and variance decomposition techniques, our result show that dynamics of equity and bond issuance in both countries vary significantly. Our findings show that there has been a two-way relationship between interest rate changes and bond issuance in the case of South Korea, whereas, stock returns have significantly influenced the bond issuance (instead of equity issuance) in Malaysia. The findings seem to support emerging popularity of corporate bond markets in Asian region.